Junie b. jones collection, books 13-16 eaudiobook - Park, Barbara (Junie B. Jones, 2006)
Read by Lana Quintal Approx. 2.5 hours 2 cassettes Available now for the first time on audio—four Junie B. Jones stories in one collection brings four times the laughs! Includes: Junie B. Jones is (almost) a Flower Girl Junie B. is tired of everyone treating her like a baby. Too bad she wasn't picked to be flower girl at her aunt Flo's wedding. Then she could really show everyone how grown-up she is. But surely she can still find some way to get everyone's attention! Junie B. Jones and the Mushy Gushy Valentine Junie B. gets a big, mushy Valentine's Day card from a secret admirer! Who is this secret mystery guy, anyway? Junie B. is determined to find out! Junie B. Jones Has a Peep in Her Pocket When Junie B.'s homeroom takes an end of year field trip to a farm, everyone is excited—except Junie B. Jones. Farms have scary ponies and scary roosters. Will there be anything good about this place or will this be the "worstest " field trip ever? Junie B. Jones is Captain Field Day Afternoon kindergarten is having a field day, and Junie B. Jones is team captain! As Captain Field Day, it's up to Junie B. to stop room eight from winning the championship. Will Junie B. find a way to lead her team to victory? Or will someone else save the day?